Die lateinische Sprache in der Musik des 20. Jahrhunderts III: Arvo Pärt - Schubert, Werner (International journal of musicology, 1997)
Arvo Pärt was born in Estonia; he is Austrian and lives in Berlin. In his musical œuvre he shows a notable preference for Latin titles and texts. Up to now, musicologists who studied Pärt's music paid less attention to the musical structure of his compositions; in the present article, some crucial compositional principles found in his Passio are discussed, as far as they are relevant to his use of the Latin language.